Rituximab toxicity in patients with peripheral blood malignant B-cell lymphocytosis - Kanelli, S; Ansell, S M; Habermann, T M; Inwards, D J; Tuinstra, N; Witzig, T E (Leukemia & lymphoma, 2001)
Infusion related adverse events (AE) with day 1 rituximab in patients with B-cell non-Hodgkin's lymphoma (NHL) are common. The purpose of this study was to evaluate the AE occurring in patients with malignant B-cell lymphocytosis who received rituximab. Patients with a > or = 3 x 10(9)/L absolute lymphocyte count (ALC) receiving rituximab from 1998 to 1999 or participating in a phase I study of rituximab and interleukin-12 were reviewed. The AE occurring on the day of rituximab, the treatment provided (including hospitalization), and the subsequent ALC responses were recorded. Twenty-seven patients were identified; 14 had NHL, one Waldenstrom's macroglobulinemia, and 12 patients had chronic lymphocytic leukemia. The baseline median ALC was 9.58 x 10(9)/L (mean, 49.31; range, 3.56-380.95). All patients received rituximab as an outpatient. There were only two AE > or = grade 3. One patient was hospitalized for 1 day for i.v. fluids to treat an increase in creatinine that occurred with tumor lysis. A second patient developed a pulmonary syndrome five days after day 1 rituximab and required mechanical ventilation, but had no long-term lung toxicity. This study demonstrates that patients with high numbers of circulating blood B-lymphocytes can usually safely receive rituximab as outpatients. Patients who experience a rapid drop in ALC should be monitored closely for tumor lysis and the pulmonary syndrome.
Keywords: Lymphocytosis; Aged; Antibodies, Monoclonal, Murine-Derived; Aged, 80 and over; lidé středního věku; senioři; Antibodies, Monoclonal; Antineoplastic Agents; lidé; Adult; Middle Aged; dospělí; Rituximab; Female; senioři nad 80 let; chronická lymfatická leukemie; Male; ženské pohlaví; Lymphoma, Mantle-Cell; monoklonální protilátky; Humans; mužské pohlaví; lymfocytóza; Leukemia, Lymphocytic, Chronic, B-Cell; lymfom z plášťových buněk; rituximab; protinádorové látky; myší monoklonální protilátky